The Management of Reprographic Right in Ghana: Efforts and Challenges - Nyadzi, Ben K. (Ghana Library Journal, 2011)
It is common knowledge that education provides the key to development in every country and Ghana is no exception. But sometimes, it is necessary to reflect on the question that if education is the key to National Development then what is the key to education itself? I think many people will agree with me that literary worksprovide the core tools and the key for the achievement of the goals of education. Quality education can hardly be successful in any country without books or literary works.